IMPLEMENTATION OF ONLINE COLLABORATIVE LEARNING IN DATABASE SYSTEMS COURSES - Nurdin Ibrahim; Sriasih; Suyitno Muslim (Journal of Islamic, Social, Economics and Development, 2022)
This study aims to determine the effectiveness of the implementation of onlinecollaborative learning in the Database System Course. Respondents in this study were secondsemesterstudents in the Undergraduate Program, Faculty of Information and CommunicationTechnology, Mataram University of Technology. The respondents used were 25 students, whowere taken from one class in the Department of Informatics Engineering. Techniques forProblem Solving were chosen as a collaborative technique by choosing one of the techniquesin it, namely Send-A-Problem. Send-A-Problem is a technique of solving a problem in groups,then forwarding the problem and its solution to the closest group who then does the same thing;the last group will evaluate all these solutions. From the results of the research conducted, itwas obtained that the average value of students from the previous 58.52 rose to 80.36 after theimplementation. There is a difference in the increase in the value of the Database System courseexam of 21,840. This indicates that student learning outcomes increase if learning is doneonline collaboratively. The results of the t-test also show the value of Sig. (2-tailed) is 0.000 <0.05, so it can be concluded that there is an average difference between the learning outcomesbefore and after, meaning that there is an influence on the implementation of onlinecollaborative in the Database System Course. The online collaborative is suggested as a wayto improve learning outcomes, which of course are not bound by space and time.